2021
DOI: 10.3390/ijms222413561
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptability and Sensory Profile of Three New Celery (Apium graveolens) Hybrids and Their Parental Genotypes

Abstract: Celery is a stalky green vegetable that is grown and consumed globally and used in many cuisines for its distinctive taste and flavour. Previous investigations identified the aroma composition of celery and profiled its sensory characteristics using a trained panel; however, evaluation of the sensory characteristics of celery combined with a consumer panel, where consumer preferences and acceptability are determined, is novel. In this study, three parental genotypes (12, 22 and 25) and three new hybrids (12x22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The results showed that the volatile compounds in celery mainly consisted of terpenes (70%). Among them, the most critical compounds were b-Myrcene, D-Limonene, b-Ocimene, and g-Terpinene, consistent with the literature (Tu and Qin, 2017;Yan et al, 2021;Turner et al, 2021a;Turner et al, 2021b). PCA analysis of 10 significantly different terpenoids found that (E)-b-Ocimene, D-Limonene, b-Myrcene and g-Terpiene were most likely to affect the compound content indicating that the difference in content between these four compounds led to differences in celery terpenoid compounds across different parts and different varieties.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that the volatile compounds in celery mainly consisted of terpenes (70%). Among them, the most critical compounds were b-Myrcene, D-Limonene, b-Ocimene, and g-Terpinene, consistent with the literature (Tu and Qin, 2017;Yan et al, 2021;Turner et al, 2021a;Turner et al, 2021b). PCA analysis of 10 significantly different terpenoids found that (E)-b-Ocimene, D-Limonene, b-Myrcene and g-Terpiene were most likely to affect the compound content indicating that the difference in content between these four compounds led to differences in celery terpenoid compounds across different parts and different varieties.…”
Section: Discussionsupporting
confidence: 89%